PERLINDUNGAN HUKUM BAGI KURIR SHOPEE DALAM SISTEM CASH ON DELIVERY - Zaidatul Asmaladiya; Sumriyah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This journal examines the legal position of couriers in the cash on delivery system in the Shopee online shopping application. The formulation of this problem involves the legal position of cash on delivery couriers in delivering to customers. Research methods include normative juridical methods by examining library materials or secondary sources, namely statutory regulations, books and legal research. The discussion includes legal protection for couriers who suffer losses in the cash on delivery transaction process. In this context, this research aims to provide recommendations to strengthen legal protection for couriers in the cash on delivery system, thereby creating a fair and safe environment for all parties involved in the online shopping distribution chain.